A socio-political history of South Africa's National Health Insurance - Eleanor Beth Whyle; Jill Olivier (BMC, 2023)
Abstract Background Spurred by the WHO's endorsement of universal health coverage as a goal of all health systems, many countries are undertaking health financing reforms. The nature of these reforms, and the policy processes by which they are achieved, will depend on context-specific factors, including the history of reform efforts and the political imperatives driving reforms. South Africa's pursuit of universal health coverage through a National Health Insurance is the latest in a nearly 100-year history of health system reform efforts shaped by social and political realities. Methods We conducted an interdisciplinary, retrospective literature review to explore how these reform efforts have unfolded, and been shaped by the contextual realities of the moment. We began the review by identifying peer-reviewed literature on health system reform in South Africa, and iteratively expanded the search through author tracking, citation tracking and purposeful searches for material on particular events or processes referenced in the initial body of evidence. Data was extracted and organised chronologically into nine periods. Results The analysis suggests that in South Africa politics; the power of the private sector; competing policy priorities and budgetary constraints; and ideas, values and ideologies have been particularly important in constraining, and sometimes spurring, health system reform efforts. Political transitions and pressures - including the introduction of apartheid in 1948, anti-apartheid opposition, the transition to democracy, and corruption and governance failures - have alternately created political imperatives for reform, and constrained reform efforts. In addition, the country's political history has given rise to dominant ideas, values and ideologies that imbue health system reform with a particular social meaning. While these ideas and values increase opposition and complicate reform efforts, they also help to expose the inequities of the current system as problematic and re-emphasise the need for reform. Conclusion Ultimately, this analysis demonstrates the context-specific nature of health system reform processes and the influence of history on what sorts of reforms are politically feasible and socially acceptable, even in the context of a global push for universal health coverage.